Integral personal and interpersonal characteristics of parents of children with complex developmental disorders - Vlasova, Olena Ivanivna; Shevchuk, Victoriya Valentynivna (Insight: the psychological dimensions of society, 2021)
The purpose of the research is to study integral personaland interpersonal characteristics of parentsbringing up children with complex developmental disorders.The article is based on the following psychodiagnosticsmethods: Parental Attitude Questionnaire(A. Varga & V. Stolin); Family Relationship Analysis(E. Eidemiller, V. Yustytskis); PARI (Parental AttitudeResearch Instrument) (E. Schaefer & Bell); FreiburgPersonality Inventory (FPI) for studying personalcharacteristics; N. Kurhanska & T.A. Nemchyn methodto assess mental activation, interest, emotional tonus,tension, and comfort; “The semantic differential” (Ch. Osgood) for quantitative and qualitative value indexing;V. Kahan & I. Zhuravlova Inventory for ParentalAttitudes to the Child’s Disease; “Sentence CompletionTest.” (J. Sacks & L. Sidney). Factorization based on principalcomponent analysis (PCA) followed by Varimaxrotation of psychological scales has made it possibleto gain a model of personal and interpersonal characteristicsof parents bringing up children with complexdevelopmental disorders. Research results. It hasbeen specified personal characteristics in the formof dominant-aggressive, psychasthenic, extraversive,sthenic-introversive personal dispositions, whichtogether form a marital subsystem. The research hasoutlined indulgent, authoritarian, constructive, phobic-indulgent, liberal-anxious educational systems thatcomprise a child-parent subsystem in the factor modelof personal and interpersonal characteristics of parents.Conclusions. It is stated that substantial natureand particularities of integral personal and interpersonalfactors, which have been noticed in parentsbringing up children with complex developmental disorders,are personal predicators of the effectivenessof their psychological follow-up.